Loss of a lake system in a megacity: the impact of urban expansion on seasonal meteorology in mexico city - Benson-Lira, V., Georgescu, M., Kaplan, S. and Vivoni, E.R. (My University, 2016)
The Mexico City Metropolitan Area (MCMA) has undergone signiﬁcant urban expansion in a closed basin that once supported a large lacustrine system. While urbanization has been mentioned as a factor in observed meteorological trends, a systematic study of the effects of land use-land cover change (LULCC) on seasonal meteorology is lacking. In this study, we utilize the Weather Research and Forecasting (WRF) system to determine the spatiotemporal changes in near-surface air temperature, precipitation, and boundary layer conditions induced by the modern-day urban landscape relative to presettlement conditions. We capture the MCMA extent through an improved Landsat-based multicategory urban classiﬁcation and therefore account for intraurban spatial heterogeneity and further conduct additional experiments to examine the sensitivity to anthropogenic heating within WRF. We ﬁnd that accounting for these factors produced the best simulations of thermal conditions, with RMSE values less than 1.5°C at all measurement stations, and an improved diurnal cycle of air temperature and precipitation. We then assessed the impacts of LULCC in the MCMA, ﬁnding that thermal changes were largest during daytime hours, with temperature increasing, on average, by more than 4°C. Furthermore, we utilize these simulations to mechanistically link the built environment-induced increase in air temperature to simulated increases in rainfall during the evening hours. To our knowledge, this study provides the ﬁrst dynamical and thermodynamical evidence to support the rainfall enhancements documented through observations in the MCMA and link it quantitatively to the warming effects associated with urbanization. These results have important implications for understanding the meteorological conditions leading to widespread urban ﬂooding in the MCMA. Highlights •Enhanced urban representation in MCMA improves simulated meteorological variables •Urbanization and loss of a lake system result in increased summer convection and rainfall •Physically based explanation between MCMA’s UHI and observed rainfall increase is provided
Keywords: Mexico City Metropolitan Area, MCMA, urbanization, land use-land cover change, LULCC, spatiotemporal changes